Pendekatan Inovativ Dalam Penanggulangan Resistensi Antibiotik di Era Globalisasi - Br Bangun, Elsi Titasari; Nada, Aina Khatrun; Jannah, Ghina Roudhotul; Khotomi, Haikal; Vaio H, Rayhan Di; Fauzan, M. Ilham; Fajar, Abdul Malik; Ramadhani, Eka; Putri, Yohana Dwi; Pratama, Randy (Jurnal Pengabdian UntukMu NegeRI, 2025)
Antibiotic resistance is a global threat that contributes to rising morbidity, mortality, and healthcare costs. Public education is a key strategy to curb resistance, particularly among the younger generation. This community service activity was carried out through a campaign on the prudent use of antibiotics at SMAN 1 Sungai Apit, Riau, involving students from grade 12 MIPA 1–4. The methods included interactive lectures, discussions, and pre-test and post-test evaluations. The results showed a significant increase in students’ knowledge regarding rational antibiotic use. These findings highlight the importance of public education, media involvement, and health system reform.